Self-emulsifying Drug Delivery Systems and their Marketed Products: A Review - Betageri, Guru V (Asian Journal of Pharmaceutics (AJP), 2019)
Self-emulsifying drug delivery systems (SEDDS) are one of the proven methods to increase solubility and bioavailability of poorly soluble drugs. SEDDS are isotropic mixtures, consisting of oils, surfactants, and sometimes cosolvents. Designed formulations are used to improve the oral absorption of highly lipophilic compounds. Multiple lipid-based drug delivery systems are widely reported in literature and they include simple oil solutions, coarse, multiple and dry emulsions, and more complex self-emulsifying, microemulsifying or nanoemulsifying drug delivery systems. The process of self-emulsification is dependent on diverse factors such as the nature of oil, surfactant, cosurfactant, oil/surfactant ratio, and the polarity of the emulsion. Considering the ease of large-scale production and the robustness of SEDDS, several formulations are commercially available which utilize this technology. This article attempts to present an overview of SEDDS along with their applications, compiled literature data, commercially available products, and their descriptions.